Environmental Factors and Personal Characteristics Interact to Yield High Performance in Domains - Subotnik, Rena Faye; Olszewski-Kubilius, Paula; Worrell, Frank C. (Frontiers in Psychology, 2019)
Outstanding human performance continues to intrigue experts and the public; however, the focus is often on the individual performer or producer with scant attention given to the additive part played by circumstances and contexts. Using general theories of development (e.g., Bronfenbrenner, 1977, 1986, 2005; Sameroff, 2010) and talent development paradigms (e.g., Dai, 2010; Subotnik, Olszewski-Kubilius, & Worrell, 2011; Ziegler, 2005), we examined the interaction of environmental and individual factors on trajectories of high performance within and across varied domains. Public and scholarly awareness of the role played by environments places greater responsibility on education and other societal systems to support talents in varied domains, and to promote evidence of talent’s malleability and potential for development.